Association between serum 25-hydroxyvitamin D level and type of coccidioidal infection. (April 2013) - Thompson, George R.; Bays, Derek; Taylor, Sandra L.; Cohen, Stuart H.; Pappagianis, Demosthenes
<x xml:space="preserve">Abstract</x> The clinical manifestations of coccidioidomycosis vary depending upon the extent of exposure and immune status of the host. Recent studies have demonstrated an essential role for vitamin D in both innate and acquired immunity and serum levels strongly correlate with the development of upper respiratory tract infections, including tuberculosis. Despite similar pathophysiologic processes at play in the control of tuberculosis and invasive fungal infections, a possible association of low serum 25(OH) vitamin D levels had not previously been assessed in the latter patient group. Therefore, we performed a case-control study examining serum 25(OH) vitamin D levels in three distinct groups of patients with coccidioidomycosis as compared to healthy uninfected controls. Of the 89 patients included in this study, there were 26 negative controls, 23 who were immune, 22 with primary coccidioidal pneumonia, and 18 who had disseminated/meningeal infection. Serum 25(OH) vitamin D levels varied between groups with lowest levels seen in the group with disseminated/meningeal coccidioidomycosis (P = 0.14). In this evaluation of a diverse group of patients with varying forms of coccidioidomycosis we found no association of vitamin D with the acquisition or resolution of this infection. Vitamin D does not play a significant role in host susceptibility to coccidioidomycosis.